Hubungan Tingkat Pengetahuan, Sikap Dan Praktik(Psp) Penderita Diabetes Mellitus Mengenai Pengelolaan Diabetes Mellitus Dengan Kendali Kadar Glukosa Darah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT The diabetes mellitus (DM) prevalence in Indonesia is continuously increasing. At present it reaches 1.4-1.6%. DM is chronic disease that is unable to recover, but it is potential to control, i.e. by managing DM appropriately so that the glucose level is controllable. DM is a disease that is related with life style